3D CBCT morphometric assessment of mental foramen in Arabic population and global comparison: imperative for invasive and non-invasive procedures in mandible. (17th February 2018) - Alam, Mohammad Khursheed; Alhabib, Selham; Alzarea, Bader K.; Irshad, Muhammad; Faruqi, Saif; Sghaireen, Mohd G.; Patil, Santosh; Basri, Rehana
Abstract: Background: Recent advancements in clinical dentistry have increased the possibilities of surgical procedures in the mental region. A detailed knowledge of mental foramen (MF) morphometry is significant to preserve integrity of the mental nerve trunk in surgical interventions such as orthognathic surgery, implant placement and anaesthetic block. Objective: The aim of this study was to determine the most accurate position of the mental foramen by using new assessment approach in a sample of dental patients presenting to the specialist dental clinic, College of Dentistry, Al Jouf University, Saudi Arabia. Study design: A retrospective study was performed using cone beam computed tomography (CBCT) of 600 patients (40.1 ± 11.78 years old). Following inclusion and exclusion criteria, 395 CBCT were finally obtained and analyzed for the most accurate position of the mental foramen (MF) by OnDemand 3D software (Seoul, Korea). Prevalence of shape of MF and accessory MF were also assessed. Pearson chi-square test was employed to test significant differences between genders and races. Results: The most common horizontal and vertical position of the mental foramen was in line with the long axis of 2nd premolar (41.3%) and below the root apex level (93.2%), respectively. The most common shape of MF was round type (72.66%). The prevalence of accessory 2MF and 3MF was 2.28% and 0.25%, respectively. Conclusion: New information about MF presented in this article can help anatomists, prosthodontists, orthodontists, surgeons, forensic odontologists and paleoanthropologists to predict the position of the MF and perform safer surgeries.